Manganese‐Catalyzed Hydrosilylation Reactions - Yang, Xiaoxu; Wang, Congyang (Chemistry, an Asian journal, 2018)
Over the past few decades, manganese‐catalyzed hydrosilylation of C=O or C=C/C≡C unsaturated bonds have undergone enormous developments. In this focus review, the hydrosilylation reactions of alkenes, alkynes, and carbonyl‐containing substrates catalyzed by manganese complexes are summarized. Moreover, the mechanisms of the manganese‐catalyzed hydrosilylation are briefly discussed. Causing a reaction: The manganese‐catalyzed hydrosilylation of alkenes, alkynes, and carbonyl‐containing substrates has developed extensively in recent years. In this focus review, hydrosilylation reactions mediated by manganese catalysts are summarized and the underlying mechanisms are discussed (see scheme).